Analysis of Fatty Acid and Protein Content in Chicken Heart Fed Maggot (Hermentia illucens) and Microalgae Aurantiochytrium sp - Anugrah, Devi; Meitiyani, Meitiyani; Hutari, Andri; Astuti, Yuni; Lestari, Suci; Prameswari, Dhanti Cynthia; Afif, Muhamad Naufal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Chicken is the most consumed food commodity in Indonesia. Chicken also contains protein which is needed by the body to maintain body strength. However, due to the Covid-19 pandemic, chicken prices have soared due to the increasingly expensive feed prices along with the increase in demand for chicken in the market. This study aims to determine the effectiveness of feeding Maggot Hermetia illucens and Microalgae Aurantiocyhtrium sp. as a source of protein and fatty acids in Joper chickens (Gallus domesticus). Using a completely randomized design (CRD) consisting of 6 treatments and 4 repetitions. Treatment P0 (100% Bran, Corn, Pur feed), P1 (Maggot 30%, microalgae Aurantiochytrium sp. 1.5%, Bran, Corn, Pur 68.5%), P2 (Maggot 35% and microalgae Aurantiochytrium sp. 2%, Bran, Maize, Pur 63%), P3 (Maggot 40% and microalgae Aurantiochytrium sp. 2.5%, Bran, Maize, Pur 57.5%), P4 (Maggot 45% and microalgae Aurantiochytrium sp. 3%, Bran, Maize, Pur 52%), P5 (Maggot 50% and microalgae Aurantiochytrium sp. 3.5%). Parameters observed were final body weight and daily weight gain rate of joper chickens. The results of this study showed that the provision of P5 treatment gave the best results in increasing protein and omega-3 levels with results of 18.19% and 4.53% respectively compared to the protein and omega-3 content of the control treatment which only amounted to 16.62% and 1.17% respectively. This study provides results with treatment P5 which has a major effect on the growth of joper chicken (Gallus domesticus). The results of this study can be an option for chicken feed because it is proven to increase protein and omega-3 content in chickens.